Technology-Assisted Informal Pragmatic Learning Among EFL Learners: Awareness, Speech Acts, And AI Tools - Dewi Cahyaningrum; Sri Haryati (Journal of Pragmatics Research, 2026)
In today’s digitally connected world, developing pragmatic competence is essential for English as a Foreign Language (EFL) learners. This competence encompasses both pragmalinguistic and sociopragmatic abilities, which are critical for using language appropriately across diverse contexts. This study explores how EFL learners informally develop pragmatic competence through digital and AI-assisted learning outside formal classroom settings. Using a qualitative descriptive approach, data were collected from 20 purposively selected Indonesian EFL learners through questionnaires and interviews. The study investigates three dimensions: learners’ pragmatic awareness and practices, types of speech acts acquired informally, and the digital tools they employ. Findings reveal that learners show a notable awareness of context-sensitive and polite language use, which is often shaped by repeated exposure to digital content. Commonly acquired speech acts include polite requests, expressions of gratitude, and compliments—frequently encountered in online media. In contrast, more complex acts such as refusals and complaints were less frequently acquired, suggesting limited exposure and the need for deeper sociopragmatic engagement. Learners demonstrated proactive engagement with digital platforms, highlighting the mediating role of technology in informal pragmatic development. Tools such as ChatGPT were valued for their dialogic simulation and personalized feedback, while Grammarly assisted with tone adjustment in written communication. Although digital tools enhance pragmatic awareness, their effectiveness in fostering sociocultural sensitivity appears limited without reflective guidance. This study underscores the need for pedagogical scaffolding to complement informal, AI-assisted learning environments.